Standardization of stem thickness and length for harvesting cinnamon (Cinnamomum verum J. Pres.) bark - P M Haldankar, B B Jadhav, M Anandaraj, R G Khandekar, U B Pethe, R N Nawale, (Journal of Spices and Aromatic Crops, 2012)
An experiment was conducted during 2008–09, 2009–10 & 2010–11 at Dapoli (Maharashtra) to study the effect of stem thickness and stem length for harvesting cinnamon bark. Twelve treatment combinations viz., two genotypes; Konkan Tej (G1), ACC-11 (G2), two lengths of stem; 50 cm (L1), 100 cm (L2) and three thicknesses of stem; 1–2 cm (T1), 2–3 cm (T2), 5–6 cm (T3) were used for experimentation. There were no significant differences in bark thickness before and after drying, fresh and dry weights of quill in the genotypes studied and length of cinnamon stem selected for bark extraction. Significantly highest bark thicknesses before (1.14 mm) and after (0.82 mm) drying and fresh (111.21 g) and dry (56.64 g) weights of quill were recorded in T3 (5–6 cm thick stem) treatment. Interaction effect of genotype, length and thickness of stem selected for coppicing indicate significant differences in bark thickness before and after drying and fresh and dry weights of quill. Significantly maximum bark thickness before drying (1.74 mm) was recorded in treatment combination G2L1T3, which was at par with G1L2T3 (1.72 mm), G2L2T3 (1.71 mm) and G1L1T3 (1.67 mm). The treatment combination G1L2T3 produced significantly highest bark thickness after drying (1.33 mm) fresh (223.31 g) and dry (117.28 g) weights of quill respectively. Significantly low bark thickness before drying (1.00 mm) fresh (49.13 g) and dry (22.92 g) weights of quill were recorded in treatment combination G1L1T1, which were at par with treatment combination G2L1T1. Higher oil percentage was observed in 5–6 cm thick stem i.e. Konkan Tej (3%) and ACC-11 (2.50%) respectively. Thus for coppicing of cinnamon for extraction of bark, harvesting of 5-6 cm thick stem is recommended.